Tkaczow a Bakunin - Kamiński, Antoni (Tkachev and Bakunin, 2008)
The paper presents "Blanąuism" represented by Russian revolutionist P. Tkachev and it compares this concept with M. Bakunin's anarchist beliefs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 31-52